PERANCANGAN E-TRAVEL GUIDEBOOK WISATA BAHARI, KABUPATEN PANGANDARAN, JAWA BARAT - Nauval, Adani (STAH Dharma Sentana Sulawesi Tengah, 2025)
Pangandaran is a leading tourist destination in West Java that is rich in natural and cultural potential. However, the lack of integrated tourist information often makes it difficult for tourists to get comprehensive guidance. This research aims to design an E-Travel Guidebook that provides complete, practical, and easily accessible tourist information. The guide includes data on tourist attractions, facilities, accessibility, and tourism services in Pangandaran. The E-Travel Guidebook is designed to assist tourists in planning trips, obtaining destination information, and enjoying a better tourist experience. This guide can also be accessed online or offline, making it more flexible. Through the utilization of digital technology, the E-Travel Guidebook is expected to increase tourist convenience and support the sustainable development of Pangandaran tourism.